Research on detection and location of weak edge signals - Xiuyun, Zhou; Xiaohan, Cao; Ting, Zhou; Zhen, Liu (Signal, image and video processing, 2020)
In order to be able to control the growth rate of industrial polycrystalline silicon rods well and reduce energy consumption, it is necessary to accurately locate the boundaries of the silicon rods and measure the diameter of the silicon rod during growth. In this paper, a weak edge signal detection method based on small area is proposed for the problem of weak boundary signal in the late growth stage of polycrystalline silicon rods. The method increases the gradient of the edge by projecting the boundary signal in the column direction. In addition, the method further enhances the gradient information of the weak boundary signal by improving the classical difference operator. In the experimental part, the improved difference operator increases the weak difference signal value from 304 to 686. Finally, the effectiveness of the algorithm is proved by two groups of experimental results.